LAMPADENA IONICA: A NEW TELEOST FROM THE MEDITERRANEAN PLEISTOCENE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The new species Lampadena ionica (Myctophidae, Teleostei) is described from lower and middle Pleistocene deposits of Southern Italy. In particular, L. ionica is known from the "large Gephyrocapsa" up to the Pseudoemiliania lacunosa biozone. Apparently the species became extinct before the end of the Pleistocene. Although the genus Lampadena lives only outside the Mediterranean today, it is known from the Mediterranean realm since the early Miocene. L. ionica seems to be the only species of the genus Lampadena existing in Pleistocene deposits of the Mediterranean area.